IDEAL COMBINATIONS OF GOVERNMENT SYSTEM AND PARTY SYSTEM FOR STABILITY AND EFFECTIVENESS OF THE GOVERNMENT - Widayati Widayati; winanto winanto (Jurnal Pembaharuan Hukum, 2019)
Indonesia since before independence until the time the core adopted a multi-party system. While the system of government changes, from a presidential, parliamentary, quasi presidential system. Multiparty presidential government systems can disrupt the stability and effectiveness of the government because there must be a coalition of political parties in the government, the preparation of the cabinet by the President must consider and accommodate the interests of coalition political parties, decision making or policy-making must also consider the interests of coalition political parties, so it will require longer time. The coalition of political parties is very fluid and pragmatic, so there may be a change in the coalition because there is a possibility that political parties that were outside the coalition will then enter the government coalition, and vice versa. Exit the entry of political parties in the government coalition will certainly be very disturbing, because political parties who have just joined the government will demand a seat in the government, especially in the cabinet. Unloading pairs of the cabinet or dismantling pairs of government seats will often occur. This of course greatly disrupts the stability and effectiveness of government. Therefore, a presidential government system ideally does not combine with a multi-party system. A change from a multi-party system to a simple multi-party system is needed, or if possible with a two-party system.